Molecular Diagnostics, Targeted Therapy, and the Indication for Allogeneic Stem Cell Transplantation in Acute Lymphoblastic Leukemia - Anthony Oyekunle; Torsten Haferlach; Nicolaus Kröger; Evgeny Klyuchnikov; Axel Rolf Zander; Susanne Schnittger; Ulrike Bacher (Advances in Hematology)
In recent years, the panel of known molecular mutations in acute lymphoblastic leukemia (ALL) has been continuously increased. In Philadelphia-positive ALL, deletions of the IKZF1 gene were identified as prognostically adverse factors. These improved insights in the molecular background and the clinical heterogeneity of distinct cytogenetic subgroups may allow most differentiated therapeutic decisions, for example, with respect to the indication to allogeneic HSCT within genetically defined ALL subtypes. Quantitative real-time PCR allows highly sensitive monitoring of the minimal residual disease (MRD) load, either based on reciprocal gene fusions or immune gene rearrangements. Molecular diagnostics provided the basis for targeted therapy concepts, for example, combining the tyrosine kinase inhibitor imatinib with chemotherapy in patients with Philadelphia-positive ALL. Screening for BCR-ABL1 mutations in Philadelphia-positive ALL allows to identify patients who may benefit from second-generation tyrosine kinase inhibitors or from novel compounds targeting the T315I mutation. Considering the central role of the molecular techniques for the management of patients with ALL, efforts should be made to facilitate and harmonize immunophenotyping, cytogenetics, and molecular mutation screening. Furthermore, the potential of high-throughput sequencing should be evaluated for diagnosis and follow-up of patients with B-lineage ALL.